Kepemimpinan Kepala Sekolah dalam Pemberdayaan Sumber Daya Manusia di SD Djama'atul Ichwan Surakarta - luthfiyah kurniawati, luthfy; Prof. Dr. Bambang Sumardjoko, Prof. Dr. Bambang Sumardjoko; Dr. Sofyan Anif, M.Si, Dr. Sofyan Anif, M.Si (2016)
ABSTRACT LUTHFIYAH KURNIAWATI, Q 100140045. PRINCIPAL OF LEADERSHIP IN THE EMPOWERMENT OF HUMAN RESOURCES AT THE PRIMARY SCHOOL DJAMA'ATUL ICHWAN SURAKARTA. THESIS. UNIVERSITAS MUHAMMADIYAH SURAKARTA. 2016 The purpose of the research to describe principal leadership in the empowerment of Teachers, to describe principal leadership in the empowerment of Students and to describe principal leadership desired of committed of school in the empowerment of human resources at the primary school Djama'atul Ichwan Surakarta. Qualitative research with ethnographic design. The place of research in primary school Djama'atul Ichwan Surakarta. When the study began in December until May. The subject of research principal, teachers, School Committee and Students. Data collection techniques using observation, interviews and documentation. The validity of the data using triangulation. Data analysis techniques with data collection, data reduction, data presentation, and conclusion. The results of the study (1) Empowerment of the Teachers in a way to involve teachers in upgrading courses or workshops and also limit Teacher minimally educated S1 (2) Principal of the Students in a way to giving the rules of school and to involve Students in competition of Regions or National (3) Style principal leadership is democratic and transformational in the empowerment of human resources. Keywords: human resources, empowerment, principal leadership